Kewajiban Sosial dalam Pemilu: Studi Hukum Islam terhadap Mencoblos semua Paslon dalam Kerangka “Mashalih Mursalah” - Muhayar, Marhadi; Uswatun Khasanah, Siti (Tasyri' : Journal of Islamic Law, 2025)
This research talks about Islamic law regarding voting for all Candidate Pairs (Paslon) within the framework of "Mashālih Murlahah". In this research, a qualitative approach was used with library data analysis (library research). The method used is deductive-inductive analysis, where researchers will develop existing theories or hypotheses based on existing principles in political, religious and legal studies, as well as data found in relevant literature. The theory used in this study is Al-Būthi's Mashālih Murlah theory. The research results show that voting for all the candidate pairs cannot be equated with not having a leader or leaving the congregation (bughāt), because in practice, even if many people vote for all the candidate pairs and their ballots are declared invalid, this will still produce a leader as regulated by the system elections and legislation. In this context, the act of voting for all candidate pairs is legally justified. However, if voting for all candidates is thought to result in winning a candidate who has the potential to bring harm to Muslims, then voting for abstention or voting for all candidate pairs is an action that is not justified (haram).